Solid-state fermentation of Palm Kernel Cake with Aspergillus flavus in laterally aerated Moving Bed Bioreactor - Yoke, Phooi Wong; Horng, Yuan Saw; Jidon Janaun; Kamatam Krishnaiah; Auti Prabhakar (2011)
Solid-state fermentation (SSF) was employed to enhance the nutritive values of palm kernel cake (PKC) for poultry feeding. Aspergillus flavus was isolated from local PKC and utilized to increase the mannose content of PKC via the degradation of ß-mannan in PKC; evaluation was done for batch SSF in Erlenmeyer flasks and in a novel laterally aerated moving bed (LAMB) bioreactor. The optimum condition for batch SSF in flasks was 110% initial moisture content, initial pH 6.0, 30 °C, 855 µm particle size, and 120 h of fermentation, yielding 90.91 mg mannose g-1 dry PKC (5.9-fold increase). Batch SSF in the LAMB at the optimum condition yielded 79.61 mg mannose g-1 dry PKC (5.5-fold increase) within just 96 h due to better heat and mass transfer when humidified air flowed radially across the PKC bed. In spite of a compromise of 12% reduction in mannose content when compared with the flasks, the LAMB facilitated good heat and mass transfer, and improved the mannose content of PKC in a shorter fermentation period. These attributes are useful for batch production of fermented PKC feed in an industrial scale.